Springback and forward slip compensation in designing roller cavity surfaces for net-shape rolling compressor blades. Issue 12 (10th September 2017) - Jin, Qichao; Wang, Wenhu; Yan, Wenyi; Jiang, Ruisong
ABSTRACT: Designing roller cavity surfaces for rolling blades is a nontrivial task. This paper presents a new method to design cavity surfaces for rolling compressor blades with considering the springback and forward slip compensation. Firstly, a springback compensation model was proposed to modify the shape of section curves, and a forward slip model was proposed to determine the location of section curves to compensate the springback and forward slip in rolling process. Secondly, an algorithm was proposed to transform the updated section curves to the cavity section curves around the roller axis. The cavities were reconstructed through the transformed section curves. Finally, the designed roller cavities for a variable cross-section compressor blade were validated by the finite element method and experiment. The results revealed that the designed cavities meet the net shape precision at pressure and suction surfaces of the blade. The compensated design of cavities for blade rolling can save both time and costs while keeping excellent design quality.